The Effectivenes of Simulation Methods to Improve Communicatio Skill in Clinical Nursing Practice : A Systematic Review - Erfan Rofiqi; Mira Triharini; Abdul Aziz Alimul Hidayat (Universitas STRADA Indonesia, 2020)
Communication is one of the competence areas that is needed by nursing students, especially in clinical nursing practice. The purpose of this study was to analyze the effect of the simulation method on improving communication skills in nursing clinical practice. Using Systematic design review. Search for articles was conducted from 29 Apri to 16 Juni 2020 by accessing five electronic databases (Scopus, Science Direct, Pubmed, Ebscohost dan ProQuest). The article year is limited from 2015-2020. Assessing the quality of articles using the JBI Critical Apprational Tool and PRISMA checklist as a guide in article screening. A total of 25 articles were analyzed according to inclusion criteria. The selected article is divided into two broad themes about simulation methods with exercises (n = 14) and simulation methods with roleplay or role-playing (n = 11). Simulation methods with exercises and roleplay or role-playing effective in improving communication skills in nursing clinical practice.